Heterogeneity of acute multiple sclerosis lesions on sodium (23Na) MRI - Eisele, Philipp; Griebe, Martin; Szabo, Kristina; Wolf, Marc; Alonso, Angelika; Ebert, Anne; Roßmanith, Christina; Hennerici, Michael G.; Schad, Lothar R.; Gass, Achim (Multiple sclerosis journal, 2016)
Background: Advanced magnetic resonance imaging (MRI) techniques provide a window into pathological processes in multiple sclerosis (MS). Nevertheless, to date only few studies have performed sodium MRI in MS. Objectives: We analysed total sodium concentration (TSC) in hyperacute, acute and chronic lesions in MS with 23Na MRI. Methods: 23Na MRI and 1H MRI were performed in 65 MS patients and 10 healthy controls (HC). Mean TSC was quantified in all MS lesions with a diameter of >5 mm and in the normal appearing white and grey matter (NAWM, NAGM). Results: TSC in the NAWM and the NAGM of MS patients was significantly higher compared to HC (WM: 37.51 ± 2.65 mM versus 35.17 ± 3.40 mM; GM: 43.64 ± 2.75 mM versus 40.09 ± 4.64 mM). Acute and chronic MS lesions showed elevated TSC levels of different extent (contrast-enhancing lesions (49.07 ± 6.99 mM), T1 hypointense lesions (45.06 ± 6.26 mM) and remaining T1 isointense lesions (39.88 ± 5.54 mM)). However, non-enhancing hyperacute lesions with a reduced apparent diffusion coefficient showed a TSC comparable to the NAWM (37.22 ± 4.62 mM). Conclusions: TSC is not only a sensitive marker of the severity of chronic tissue abnormalities in MS but is also highly sensitive to opening of the blood-brain barrier and vasogenic tissue oedema in contrast-enhancing lesions.
Gesehen am 05.07.2019
First Published October 9, 2015
Im Titel ist die Zahl "23" hochgestellt